Repercussão clínica da angiotomografia coronariana em pacientes sem coronariopatia documentada - Naue, Vânia Mairi (2014)
Introduction: Coronary computed tomography angiography (CCTA) allows for noninvasive coronary artery disease (CAD) phenotyping. There are still some uncertainties regarding the impact this knowledge has on the clinical care of patients. Objective: To determine whether CAD phenotyping by CCTA influences clinical decision making by the prescription of cardiovascular drugs and their impact on non- LDL cholesterol (NLDLC) levels. Methods: We analysed consecutive patients from 2008 to 2011 submitted to CCTA without previous diagnosis of CAD that had two serial measures of NLDLC, one up to 3 months before CCTA and the second from 3 to 6 months after. Results: A total of 97 patients were included, of which 69% were men, mean age 64±12 years. CCTA revealed that 18 (18%) patients had no CAD, 38 (39%) had nonobstructive (<50%) lesions and 42 (43%) had at least one obstructive ≥50% lesion. NLDLC was similar at baseline between the grups (138±52 mg/dl vs. 135±42 mg/dl vs. 131±44 mg/dl, respectively, p=0.32). We found significative reduction in NLDLC among patients with obstrctive lesions (-18%, p=0.001). We also found a positive relationship between clinical treatment intensification with aspirin and cholesterol reducing drugs and the severity of CAD. Conclusions: Our data suggest that CCTA results were used for cardiovascular clinical treatment titration, with especial intensification seen in patients with obstructive ≥50% CAD.